Sandstone Provenance of Walanae Formation as a Parent Rock in Bulukumpa area, Bulukumba Regency, South Sulawesi: Provenance Batupasir Formasi Walanae sebagai Bahan Induk Tanah di Daerah Bulukumpa Kabupaten Bulukumba, Sulawesi Selatan - Farida, Meutia; Burhan, Moh. Junaedy; Umar, Hamid; Imran, A M; Ikhwana, Nur; Ahmad, Asmita (Universitas Hasanuddin, 2023)
The Walanae Formation has a wide distribution in the southern arm of Sulawesi, this rock formation was deposited during the formation of the basin due to the Walanae strike-slip fault. The Walanae Formation in the study area comprises sedimentary rocks and pyroclastic rocks, which give different soil characteristics. This study aims to determine the types of sandstones, rocks of origin, and provenance of sandstones in the study area by using spot sampling at representative stations and petrographic analysis. The sandstones of the study area are divided into two groups based on Folk (1974), namely arkose lithic and feldspathic litharenite. Based on the type of quartz, rock fragments, and associated minerals, the origin of the sandstones in the study area are plutonic igneous rocks, volcanic rocks, sedimentary rocks, and metamorphic rocks. The results show that the types of provenance sandstones in the study area are magmatic arc and recycled orogenic.